2012
DOI: 10.1542/peds.2011-3588
|View full text |Cite
|
Sign up to set email alerts
|

Food Insecurity and Obesogenic Maternal Infant Feeding Styles and Practices in Low-Income Families

Abstract: WHAT'S KNOWN ON THIS SUBJECT: Food insecurity has been linked to childhood obesity in a number of studies. Few studies have explored potential pathways through which food insecurity is related to child weight, especially in low-income families with young infants. WHAT THIS STUDY ADDS:We found that food insecurity was related to maternal controlling feeding styles and concerns about the infants' future weight. Early obesity prevention should aim to decrease food insecurity and to reduce controlling feeding styl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
89
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(93 citation statements)
references
References 52 publications
4
89
0
Order By: Relevance
“…The findings were consistent with a study in Nepal that suggested that parent's educational status and socio-economic status were significantly associated with HHFI. 18 Similar results have been observed in Organization for Economic Co-operation and Development (OECD) countries, such as, The Unites States of America; households with illiterate mothers are vulnerable to food insecurity 29 . Illiterate mothers with poor socioeconomic status reflect inadequate CFP.…”
Section: Prevalence Of Hhfi (Bivariate Analysis Based On Chisquare Test)supporting
confidence: 66%
See 1 more Smart Citation
“…The findings were consistent with a study in Nepal that suggested that parent's educational status and socio-economic status were significantly associated with HHFI. 18 Similar results have been observed in Organization for Economic Co-operation and Development (OECD) countries, such as, The Unites States of America; households with illiterate mothers are vulnerable to food insecurity 29 . Illiterate mothers with poor socioeconomic status reflect inadequate CFP.…”
Section: Prevalence Of Hhfi (Bivariate Analysis Based On Chisquare Test)supporting
confidence: 66%
“…Nevertheless, in The United States of America, the introduction of juice and HHFS did not show any significant association. 29 Insufficient domestic production of non-cereal foods (for example, pulses, fruits, meat, milk, eggs etc. ), lower socio-economic status, and lack of nutritional knowledge reflect HHFI.…”
Section: Discussionmentioning
confidence: 99%
“…There is also early evidence that poverty and food insecurity may affect feeding practices from early infancy, with decreased rates of breastfeeding and higher use of controlling feeding styles, such as pressure on infants to feed and restriction of infant intake. 10,34 Though children in food insecure households may be protected from hunger as a result of the sacrifices of their caregivers, 32 there may still be changes in feeding behaviours that could influence child health. A better understanding of the mechanisms behind these associations, particularly in very young children, may point to targeted nutrition interventions at both the clinical and population health levels.…”
Section: Discussionmentioning
confidence: 99%
“…9 Recent studies have also indicated that food insecurity may lead to obesogenic feeding behaviours, such as restriction of food and pressure to eat, in infants. 10 However, studies examining food insecurity as a predictor of obesity in young children have shown conflicting results.…”
mentioning
confidence: 99%
“…While the sample's feeding choices are similar to a broader sample of women, The lack of association between parenting style and infant dietary intake may be due to not measuring the demandingness dimension of parenting style, although similar methodology used elsewhere 58 did detect relationships. Modification of the CFQ restriction questions to better measure transitional feeding practices may have affected the relationships detected, though this is not the first time the CFQ has been modified, 17,277,278 specifically around the restriction subscale. 279 The association between pressure-to-eat and both low birth and low current weight would suggest an infant-led interaction.…”
Section: Strengths and Limitationsmentioning
confidence: 99%